Kombinasi Mixer Audio Multitrack 4 Channel Dengan Software Digital Audio Workstation Mixcraft 9 Pro Studio Yang Dilengkapi Desible Peak Meter - Aditio Fahrul Anam; Didik Aribowo; Desmira (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to design and test the performance of a 4-channel analog multitrack audio mixer combination system that is integrated with the Digital Audio Workstation (DAW) of Mixcraft 9 Pro Studio and equipped with a decibel peak meter. The research method uses a descriptive, evaluative, and experimental approach through the stages of literature study, tool design, testing, and data processing. The test was conducted using the recording of the Unreal Verse Episode 5 Podcast on several variations of duration and four frequency filter modes, namely FLAT, LOW CUT, MID CUT, and HIGH CUT. The parameters analyzed included sound intensity (W/m²) and output voltage (mV). The test results showed that the FLAT configuration produced the best performance with a sound intensity of 0.0588 W/m² and a voltage of 167.7 mV. At longer playback durations, the system achieves a maximum value of intensity of 0.0631 W/m² and a voltage of 207.83 mV. Low- and medium-frequency cuts have a significant impact on signal energy degradation. These findings prove that the integration of analog mixers and DAWs can function effectively as efficient and applicable digital mixers for podcast production and mid-range audio installations. Keywords: Audio Mixer, DAW, Multitrack, Sound Intensity, Audio Voltage.